Outcome of Primary CNS Lymphoma; A Retrospective Analysis - Shahzadi, Mehwish; Ahmed, Daniyaal; Sawani, Sobia; Moosajee, Munira (Asian Pacific Journal of Cancer Care, 2022)
Background: Rituximab along with high dose Methotrexate is nowadays the standard of care in treatment of PCNSL. We report the retrospective analysis of PCNSL patients who were treated with and without Rituximab at Aga Khan University Hospital, Karachi. Patients and Methods: While analyzing seven years’ data of PCNSL patients at Aga Khan University hospital, 52 patients encounter this rare disease. Patients diagnosed were around 54 years of age and with male predominance. HIV status though checked in 50% of patient was found to be negative in all. 36 patients completed treatment and among them 60% patients could not receive Rituximab during the course of treatment with high cost being the only reason of not receiving anti-CD 20 monoclonal antibody. Radiation as a part of consolidation therapy was received by 20 patients who achieved CR followed by two cycles of Cytarabine. Results: Out of 36 treated patients, 17% patients (6 out of 36) had disease progression. The median progression free survival was 51 months (Hazard Ratio of 0.594, 95% Confidence Interval CI, 0.182, 1.934; p < 0.388). The addition of Rituximab monoclonal antibody to the chemotherapy regimen improved the PFS. However, 41% patients (9 out of 22) who did not receive Rituximab had no response after induction as compared to 29% patients (4 out of 14) who received Rituximab. The mean overall survival of treated PCNSL patients was 67 months (Hazard Ratio of 8.52, 95% CI 0.974, 74.51, p< 0.053). Within the cohort of 36 patients, 61% patients (22 out of 36) were still alive at the time of analysis. Among 39% who were dead, the most common causes were sepsis and progression of disease. Conclusion: Primary CNS lymphoma though an aggressive entity can be cured with the combination of chemo-immunotherapy with a progression free survival and overall survival of about four to five years.